2019
DOI: 10.12688/f1000research.19217.1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of malaria and quantification of cytokine levels during infection in East Nile locality, Khartoum State: a cross-sectional study

Abstract: Background: The cytokines interferon gamma (IFN-γ), interleukin-10 (IL-10) and tumor necrosis factor-α (TNF- α) play an important role in malaria infection. The aim of this study was to determine the prevalence of malaria and to evaluate cytokine responses to malaria infection in patients from the East Nile locality of Khartoum State. Methods: This study was carried out from May to July 2018 in the East Nile Locality, Khartoum State. Blood samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
1
3
1
Order By: Relevance
“…Ethiopia is one of the sub-Saharan countries highly endemic to malaria where an estimated 68% of the population lives in malarious areas [ 4 , 5 ]. In the present study, the prevalence of microscopically confirmed malaria cases was 17.3% which is similar to studies conducted in the Zeway Health Center, Ethiopia (17%) [ 22 ], Gurage Zone, Southern Ethiopia (18.3%) [ 23 ], East Nile locality of Khartoum State (18.5%) [ 24 ], and Kenya (15.5%) [ 25 ]. However, the finding of this study is lower than studies conducted in Arba Minch, Southern Ethiopia (27.6%) [ 20 ], Kersa Woreda, Ethiopia (43.8%) [ 26 ], Zaria, Nigeria (45.4%) [ 27 ], and New Delhi (24%) [ 18 ] and higher than studies conducted in North Shoa, Ethiopia (8.4%), and District Dir Lower, Pakistan (12.2%) [ 28 , 29 ].…”
Section: Discussionsupporting
confidence: 87%
“…Ethiopia is one of the sub-Saharan countries highly endemic to malaria where an estimated 68% of the population lives in malarious areas [ 4 , 5 ]. In the present study, the prevalence of microscopically confirmed malaria cases was 17.3% which is similar to studies conducted in the Zeway Health Center, Ethiopia (17%) [ 22 ], Gurage Zone, Southern Ethiopia (18.3%) [ 23 ], East Nile locality of Khartoum State (18.5%) [ 24 ], and Kenya (15.5%) [ 25 ]. However, the finding of this study is lower than studies conducted in Arba Minch, Southern Ethiopia (27.6%) [ 20 ], Kersa Woreda, Ethiopia (43.8%) [ 26 ], Zaria, Nigeria (45.4%) [ 27 ], and New Delhi (24%) [ 18 ] and higher than studies conducted in North Shoa, Ethiopia (8.4%), and District Dir Lower, Pakistan (12.2%) [ 28 , 29 ].…”
Section: Discussionsupporting
confidence: 87%
“…The prevalence rate of P. falciparum infection observed among the pregnant women in this study is 31.9%, which is lower than the rates of 40%, 60%, 78.4%, and 92% reported in Abia and Gombe State Nigeria, respectively (Ali, 2022;Ejike et al, 2017;Shaibu et al, 2019;Yoriyo and Hafsat, 2014). Additionally, the prevalence rate is higher than the rates of 18.5% and 19.5% reported in Sudan and Lagos Nigeria, respectively (Barkat et al, 2019;Olukosi and Afolabi, 2018). The difference in the prevalence rate in this study compared to the previous studies could be due to the difference in regions, time and season in which the studies were conducted and the environmental conditions which harbours the breading site of the intermediate host in the study area.…”
Section: Discussioncontrasting
confidence: 73%
“…The early recreation of inflammatory reaction induced by IFN-γ and IL-12. TNF-α appears to be essential for parasite clearance and parasitemia control in malaria infection (Barkat et al, 2019). The high production of pro-inflammatory cytokines is associated with severe malaria and these may increase adherence of parasitized red blood cells to the endothelium through upregulation of adhesion molecules in P. falciparum infections (Barkat et al, 2019;Malaguarnera & Musumeci, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, significant elevated level of proinflammatory IL-6 and IL-10 was reported in Malian children with severe-malaria [38,39]. In addition, a Sudanese study reported high level of IL-10 was reported among malaria parasitemic children [40].…”
Section: Discussionmentioning
confidence: 83%